Why locate manufacturing in a high-cost country? A case study of 35 production location decisions - Turkulainen, Virpi; Seppälä, Timo; Rouvinen, Petri; Ali Yrkkö, Jyrki; Ketokivi, Mikko (Elsevier B.V., 2017)
In this paper,we examine in detail 35 final assembly location decisions to gain understanding of the manufacturing location decision from strategy and economic policy perspectives. We are particularly interested in the decision to locate final assembly specifically in a high-cost (high GDP per capita) environment. In contrast with the earlier literature,we focus not just on manufacturing activities themselves,but also the key linkages between production,market,supply chain,and product development. These linkages are examined using three key concepts from theories of organization design: formalization,specificity,and coupling. Using these concepts,an analysis of the micro-structure of each case reveals important commonalities that inform our understanding of location decisions. We conclude by discussing the policy implications of our findings. © 2017 Elsevier B.V.
Keywords: Location; Manufacture; Planning; Public policy; Case-studies; Economic policies; Final assembly; High cost countries; High costs; International operations; Location decisions; Manufacturing location decision; Per capita; Production locations; Supply chain management; Case study; International operations; Manufacturing location decisions; Supply chain management